Utilization of Information Systems in Handling the Spread of Hoaxes (Pinisi Journal of Officers Review, 2024)
The use of information systems in handling the spread of hoaxes at the Makassar City Communication and Information Office. This research is a qualitative descriptive research that aims to find out the Utilization of Information Systems in Handling the Spread of Hoaxes in the Makassar Diskominfo. The number of informants in this study was 5 people, namely 2 heads of fields from the war room and Public Information and Communication fields, 1 CCTV team leader, 1 from 112 operators, 1 from facility management employees. The data collection technique uses observation methods, interview methods, and documentation methods. The data analysis technique in this study uses data reduction techniques, data presentation, conclusion and verification. The results of this study show that the use of information systems at Diskominfo Makassar arises because of the lack of tools needed, namely applications that can connect directly between employees and the community to facilitate direct communication such as applications that have been provided in the past but have been discontinued because the application has a budget. This research can be used as a reference and knowledge about the use of information systems in more depth because unlike previous research that used quantitative methods that focused on numbers and statistics, this research uses qualitative methods that produce more detailed descriptions of information systems .